A construção do espaço pelo turismo: rota turística gastronômica de Santa Maria e Silveira Martins, RS - Torres, Thaís Gomes (2009)
Tourism is a phenomenon conveyed in the feasibility of transforming and reorganizing geographic space. Tourism reassures cultures and social values, strengthens environmental notions and creates mechanisms to make the economy of a specific place more dynamic. In order to unleash this net of relationships, Tourism needs the articulation among public policies, private sector, and local community; depending on the interrelation with many sciences. The following work aimed mainly to conduct an analysis on the transformation of the space of the municipalities Santa Maria and Silveira Martins for the Tourism at the Gastronomic Touristic Route of Santa Maria and Silveira Martins. This area was situaded at the Rio Grande do Sul state, southern Brazil at the borther of the Paraná Basin. Many authors approaching and discussing the subject of Tourism Geography, categories space and territory, as well as the role of the public power in the regional/local development have been consulted to develop the work and support it. The methodology used was the theoretical research, the study of a wide bibliography guiding the proposed topics and the collection of data. These data were obtained through field researches in the Gastronomic Touristic Route of Santa Maria and Silveira Martins, with pre set visits, reading of local newspapers, and photography storage, mapping of some attractive with the use of a Leica Global Position System and notes in a field record. In the empirical analysis of the Gastronomic Touristic Route, it was perceived that most of the offer of leisure and Tourism already existed before the establishment of the route, even though it was not organized as a touristic product. With the signing of a protocol of intentions between the two City Halls of Santa Maria and Silveira Martins, the route was established in 2005. In 2008 the Association of the Gastronomic Touristic Route was established to act in the planning and management of the route. In the discussion of the results, it was possible to notice that the Gastronomic Touristic Route presents distinct territorialities that set though many uses: local community, private sector, and public sector. The harsh and transformations of the space were important throughout the years to consolidate the route as a strong touristic product of the Central portion of the RS. It is necessary, however, an integrated action of the local community with an integrated planning of the two municipalities, in a way that it strengthens the management of the Touristic Route and contributes to for the economy to strengthen and improve the quality of life of the local population.